Errors, omissions and medication patterns of handwritten outpatient prescriptions in Bangladesh: a cross-sectional health survey - Md. Uzzal Haque, S.M. Abdul Barik, Shamiul Bashar, Rashedul Islam, Samia Bashar, Anup Kumar, Abid Hasan Dipon, Nurunnahar Kona, Aktar Uzzaman Chouduri (Journal of Applied Pharmaceutical Science, 2016)
Handwritten prescription errors are worldwide common problem. We investigated the types and extent of prescription errors in three cities of Bangladesh. Total 900 outpatient prescriptions were surveyed following the guidelines of WHO and BNF. Prescription errors in superscription, inscription and subscription were analyzed by Microsoft Excel 2010. About 73% patients visited MBBS and 8% BDS doctors. The male outpatients (55%) were slightly higher than female (45%). Commonly found errors of prescription were in superscription part, i.e. gender (64.33%), age (17.67%) and name (5%) of the patients. In inscription part, most common error was the direction for drug use (42%) followed by the dosage regimens (28%), doses (26%), and dosage forms (12.67%) of the drug. In subscription part, illegible handwriting was most common (46%) followed by the prescribers sign (10.67%) and date (4%). In a single prescription, averagely 3 and maximally 8 drugs were found to be prescribed. Most frequently prescribed drugs were antibiotics (18.25%) followed by antacids (17.45%) and NSAIDs (13.60%). Errors in handwritten prescriptions are the primary causes of treatment failure in Bangladesh. More professional care by the prescribers’ and the inclusion of pharmacists in hospital can only reduce the errors and assure safer health.
Keywords: Outpatients, doctors, handwritten prescriptions, prescription errors, Bangladesh.